The effect of different clay types on the barrier properties of PLA/PBAT/clay bio-nanocomposite packaging films - Guler, Ceren Alpaslan; Deniz, Sennur (TAYLOR & FRANCIS INC, 2023)
The aim of this study was to develop alternative bio-nanocomposite film to Polyethylene (PE) film from poly(lactic acid) (PLA) and poly(butylene adipate-co-terephthalate) (PBAT) blends and different clay types for flexible packaging industry. Poly(lactic acid)/poly(butylene adipate-co-terephthalate) (PLA/PBAT) bio-blend films were prepared by using a chain extender. Bio-nanocomposite films were processed on a twin-screw extrusion and blown film extruder by wt.%3 loading the different montmorillonite (MMT), Sepiolite, and Bentonite types in presence of a polymeric epoxy-based chain extender plasticizer (CE; Joncryl & REG; ADR 4468). All films were characterized in terms of thermal, chemically, physically, optical, mechanical, sealing and barrier properties. In conclusion, all analyzing results showed good agreement with PLA/PBAT in the presence of a polymeric epoxy-based chain extender. The main outcome of adding clay types to PLA/PBAT bio-blends is to obtain eco-friendly, improved barrier properties compared to PE film structure, which has inherently poor oxygen permeability. As a result of all studies, the closest alternative bio-blend recipes to PE film structure with improved barrier properties were obtained with composite of wt.%25 PLA + %75 PBAT in the presence of wt.%1 plasticizer and %3 High Purity Sepiolite clay (HPS).
Keywords: Clay; chain extender; poly(lactic acid) (PLA); poly(butylene adipate-co-terephthalate) (PBAT); bio-nanocomposite; BLENDS; Chemistry